2021
DOI: 10.1038/s41598-020-79208-y
|View full text |Cite
|
Sign up to set email alerts
|

Reduced occludin and claudin-7 expression is associated with urban locations and exposure to second-hand smoke in allergic rhinitis patients

Abstract: The breakdown of nasal epithelial barrier occurs in allergic rhinitis (AR) patients. Impairment of cell junction molecules including tight junctions (TJs) and desmosomes plays causative roles in the pathogenesis of AR. In this study, we investigated the transcript expression levels of TJs including occludin (OCLN), claudin-3 and -7 (CLDN3 and CLDN7), desmoglein 3 (DSG3) and thymic stromal lymphopoietin (TSLP) in AR patients (n = 30) and non-allergic controls (n = 30). Nasal epithelial cells of non-allergic con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
0
14
0
1
Order By: Relevance
“…We acknowledge the limitations of the study as follows: (1) Small sample size; (2) Sample size calculation had been conducted previously according to past gene expression studies, but not studies pertaining to SPT wheal sizes in AR patients, as this study was part of our previously published cross-sectional gene expression study (23); (3) Lack of correlation studies with other symptom questionnaires such as the total nasal symptom score (TNSS) (44)(45)(46), or with the levels of total and specific IgE. Future investigations addressing these limitations are thus recommended.…”
Section: Discussionmentioning
confidence: 99%
“…We acknowledge the limitations of the study as follows: (1) Small sample size; (2) Sample size calculation had been conducted previously according to past gene expression studies, but not studies pertaining to SPT wheal sizes in AR patients, as this study was part of our previously published cross-sectional gene expression study (23); (3) Lack of correlation studies with other symptom questionnaires such as the total nasal symptom score (TNSS) (44)(45)(46), or with the levels of total and specific IgE. Future investigations addressing these limitations are thus recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown the defect in epithelial barrier due to decreased expression of CLDNs that contribute to AR in both patients and animal models. Recently, we demonstrated a decreased expression of CLDN3 and CLDN7 in nasal epithelial cells (NECs) of HDM-induced AR patients compared to nonallergic controls (34). CLDN1, CLDN3, CLDN7 and CLDN12 mRNA and protein expressions were significantly decreased in nasal epithelium of AR patients compared to controls subject (32).…”
Section: Claudinsmentioning
confidence: 98%
“…Nasal epithelial barrier function has been known to be impaired in HDM-induced AR patients (33). Lower OCLN mRNA expression also occurred in HDM-induced AR patients compared to non-allergic controls (33,34). Moreover, reduced ordered arrangement of OCLN was found in AR patients and the defect might expedite the passage of allergens and environmental pro-inflammatory agents through nasal epithelial barrier (33).…”
Section: Disruption Of Tight Junctions In Ar Occludinmentioning
confidence: 99%
See 1 more Smart Citation
“…Оказалось, что некоторые респираторные вирусы способны сдвигать баланс иммунной системы человека в сторону Th2-ответа, что может стать одним из факторов риска развития и/или обострения бронхиальной астмы. Чаще всего этот феномен наблюдается у детей с частыми (более 6 раз в год) респираторными инфекциями, при инфицировании риновирусами и респираторно-синтициальными вирусами [11,12].…”
unclassified